Proliferation of Faulty Materials Data Analysis in the Literature - Linford, Matthew R.; Smentkowski, Vincent S.; Grant, John T.; Brundle, C. Richard; Sherwood, Peter M.A.; Biesinger, Mark C.; Terry, Jeff; Artyushkova, Kateryna; Herrera-Gómez, Alberto; Tougaard, Sven; Skinner, William; Pireaux, Jean-Jacques; et al. (Microscopy and microanalysis, 2020)
As a group of subject matter experts in X-ray photoelectron spectroscopy (XPS), we write this letter to raise awareness of the epidemic of poor and incorrect materials data analysis in the Literature. This is a chronic and growing problem with very undesirable consequences. This issue may contribute to what has been identified as a “reproducibility crisis”1,2 that was the subject of a recent U.S. National Academies study. We are using XPS as one example of what we observe to be a systemic issue.